(untitled) (Global Journal of Human-Social Science, 2020)
The article intends to demonstrate how the citizenship was defined in Brazil of the First Republic, by verifying how parallel discourses and realities are developed in this process: on one side an official discourse that aimed to implant an European-like and excluding reality, conciliating political liberalism with racial discourses, both guarantees of legitimacy and modernity; on the other side, the language and the popular culture that emerged from the relationships of belonging constructed in the quotidian of the marginalized layers by the official discourse. Both say and construct what used to be one of the central questions of the republican thinkers in the end of XIX century and beginning of the XX century: what it is and what defines the Brazilian people.